Preparation and pharmacological evaluation of enantiomers of certain nonoxygenated aporphines: (+)- and (-)-aporphine and (+)- and (-)-10-methylaporphine - Cannon, Joseph G; Raghupathi, Revathi; Moe, Scott T; Johnson, Alan K; Long, John Paul (Journal of medicinal chemistry, 1993)
The subject compounds were prepared as a part of a continuing structure-activity study of the contrasting actions (agonism-antagonism) of (+)- and (-)-11-hydroxy-10-methylaporphine at serotonin (5-HT1A) receptors. None of the targeted nonoxygenated aporphine derivatives demonstrated significant activity in assays for any effects at serotonin 5-HT1A receptors. It is concluded that, in the aporphine series, serotonergic agonist or antagonism requires an alkyl group ortho to a phenolic OH group in the A ring.